Stigma, Ableism and Social Identity: Whose Disability? - Teixeira-Machado, Lavínia (Advances in Social Sciences Research Journal, 2025)
This article presents a theoretical and critical essay that explores central themes, including stigma, ableism, and social identity, and situates them within contemporary agendas on human rights, inclusion, and social justice. Structured as a historical, conceptual, and comparative review, it integrates classical contributions (Goffman, Oliver, Tajfel, and Turner) with recent literature in Social Psychology, Sociology, and Disability Studies. The analysis highlights how ableism is socially and structurally embedded, shaping persistent barriers to participation and autonomy for persons with disabilities (PwD). By examining the tensions between identity, exclusion, and inclusion, the essay reveals the contradictions that sustain discrimination and marginalization. It also emphasizes the need for critical reflection and structural transformation to mitigate ableist practices and to foster societies that genuinely recognize and value human diversity.